PROPUESTA DE UN PLAN DE MARKETING TURÍSTICO PARA LAS FIESTAS RELIGIOSAS DE LA CIUDAD DE LOJA - JIMÉNEZ QUITUISACA, RICARDO ANDRÉS (2016)
Tourism has become one of the main factors of international trade is a major source of income for many developing countries, tourism is developing on a large scale throughout the world, which are using different strategies oriented advertising and creativity such as tourism marketing, in order to reach the most people. The Ministry of Tourism of Ecuador, it known that the southern region of Ecuador made up of the provinces of Loja, El Oro en Zamora Chinchipe are formed in a single socio-economic community, the province of Loja being the historical and cultural center of the region, the Province Loja called the "Sentinel of the South" for its unique beauty and cultural traditions is one of the main attractions that the country has. Within the province, the city of Loja, characterized by its cultural events, such as the celebration of religious festivals, which are held every year in the church of each urban parish of the city, stands unfortunately these parties do not have proper promotion to generate a tourism impact on society, that is why through the implementation of a marketing plan for the religious festivals of the city, can generate a very important factor for socioeconomic development. To prepare the marketing plan for the religious festivals of the city of Loja three specific objectives are developed: A diagnosis of the current situation of the city of Loja, where the current RealD Country and City will be discussed in this objective different methods and techniques used, as is the interview which was made exclusively for Priests of the main churches of the city of Loja, and the survey was aimed at families in general population of Loja, it is also a SWOT matrix which could indicate the strengths, weaknesses, opportunities and threats that religious festivals was prepared also thanks to the SWOT matrix could determine the strategic objectives to develop the proposal. The second objective is to propose a marketing plan for Religious celebrations of the city of Loja, in which two strategic objectives were made. The first strategic objective is: "Making a Plan Advertising and Promotion, which allows positioning the religious festivals of the city of Loja" as a tourist to visit in order to increase the number of visitors place; to develop this target different types of promotion such as are performed; create a brand and slogan, brochures, totems, billboards, t calendars, souvenirs etc. The second strategic objective is to: Develop a training program to service providers in the tourism sector, in order to generate a higher level of provision that benefit the City for the development of tourism; Good Practices Training for the Tourism Service, which will last for one year and wax accredited for a period of 250 hours and which to be certified by the SECAP: to develop this goal a program with the theme was held. And finally we have the last specific objective was the socialization of the proposal was aimed at officials of Tourism of the Municipality of Loja, where we know what their opinions about the work, to which they knew we say that it is an interesting project which, besides being an interesting idea can be executed because it can contribute to the development of religious tourism as it is a valuable proposal to develop is activity.